2015
DOI: 10.1007/s00244-015-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rare Earth Elements in Human Sperm and Association with Semen Quality

Abstract: The aim of the present study was to measure lanthanum (La), cerium (Ce), europium (Eu), and gadolinium (Gd) concentrations in human semen and correlate the results with sperm quality. The median semen content of La was 19.5 µg kg−1 dry weight (dw) (range 2.27–269), of Ce was 41.9 µg kg−1 dw (range 4.52 to 167), of Eu was 0.68 µg kg−1 dw (range 0.06–1.95), of Gd was 3.19 µg kg−1 dw (range 0.38–12.0), and of calcium (Ca) was 4063 mg kg−1 dw (range 484–17,191). Concentrations of La, Ce, Eu, Gd, and Ca were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Investigation of human semen indicated that the concentration of REEs in semen is negatively associated with sperm concentration (Marzec-Wróblewska et al, 2015). The observations in this study seem to support this.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Investigation of human semen indicated that the concentration of REEs in semen is negatively associated with sperm concentration (Marzec-Wróblewska et al, 2015). The observations in this study seem to support this.…”
Section: Discussionsupporting
confidence: 80%
“…Subchronic exposure to Sm caused lesions and abnormal regulation of apoptosis in the testis (Zhang et al, 2014). A recent investigation of human semen also suggested that La, Ce, Gd, and Ca concentrations in the semen are negatively associated with sperm concentration, and positively associated with the progressive motility and percentage of normal spermatozoa (Marzec-Wróblewska et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the proliferation of osteoblasts is stimulated, and the differentiation of osteoclasts is impeded during bone remodeling. [33] Lanthanides involved in many of vital processes as sperm fertility, [34] anti-HIV activities, [35] and antidiabetic. [25,26] Moreover, Lanthanides have been reported in the treatment of renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] In addition, Lanthanides exerted many of biological activity as antioxidant, [29] antiseptic, [30] antibacterial, [25,31] anticoagulant, [32] and antiparasites. [33] Lanthanides involved in many of vital processes as sperm fertility, [34] anti-HIV activities, [35] and antidiabetic. [32,36] The study included some factors related to cell survival as TNF R2, CCN1/CYR61, and Cyt c. Tumor necrosis factor receptor II (TNF R2) has antiapoptotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Both mainstream and sidestream smoke contain many toxic elements including heavy metals and rare earth elements (Böhlandt et al, 2012;Slezakova et al, 2009). The components of tobacco smoke are known as affecting both the semen characteristics and the individual sperm parameters (Böhlandt et al, 2012;Marzec-Wróblewska et al, 2015a;Pant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%